Strategy in a world of sustainability: A developmental framework - Galbreath, Jeremy (Graduate School of Business, Curtin University of Technology, 2008)
Sustainability is a business approach that seeks to create long-term value by embracing the opportunities and the managing risks associated with economic, environmental and social developments. However, little guidance is available to assist firms in developing strategy, given the realities of sustainability. By taking an issues perspective and strategy development approach, this paper proposes a developmental framework for creating strategy in a world of sustainability.A case study is offered to highlight the use of the framework.